Cognitive Function and Sleep in Caregivers of Persons Living with Dementia. (March 2022) - Brewster, Glenna S.; Molinari, Victor; McCrae, Christina; Beckstead, Jason; D'Aoust, Rita; Rowe, Meredeth
Poor sleep is prevalent among caregivers of persons living with dementia and increases their risk for cognitive impairment and decline. In this cross-sectional, correlational study, we compared the cognitive function scores of caregivers with poor sleep with the demographically adjusted normed scores of the National Institutes of Health Toolbox Cognition Battery. Caregivers completed a 14-day sleep diary. On average, caregivers (n = 28) were 65.14 (±10.08) years, female, and White. Their average crystallized cognitive function composite score was significantly higher and their average fluid cognitive function composite score was significantly lower than the normative scores. Caregivers performed significantly worse on the processing speed domain measure. Poor sleep may affect how caregivers, including highly educated caregivers, process and respond to information, thus can influence how they safely perform complex caregiving tasks. Health care providers should consistently assess caregivers' sleep and cognitive abilities to promptly identify changes and provide timely interventions.